BK Polyomavirus‐Specific 9mer CD8 T Cell Responses Correlate With Clearance of BK Viremia in Kidney Transplant Recipients: First Report From the Swiss Transplant Cohort Study. Issue 10 (25th April 2017) - Leboeuf, C.; Wilk, S.; Achermann, R.; Binet, I.; Golshayan, D.; Hadaya, K.; Hirzel, C.; Hoffmann, M.; Huynh‐Do, U.; Koller, M. T.; Manuel, O.; Mueller, N. J.; et al.
Abstract : BK polyomavirus (BKPyV) causes premature kidney transplant (KT) failure in 1–15% of patients. Because antivirals are lacking, most programs screen for BKPyV‐viremia and, if positive, reduce immunosuppression. To evaluate the relationship of viremia and BKPyV‐specific immunity, we examined prospectively cryopreserved plasma and peripheral blood mononuclear cells at the time of transplantation (T0) and at 6 mo (T6) and 12 mo (T12) after transplant from 28 viremic KT patients and 68 nonviremic controls matched for the transplantation period. BKPyV IgG seroprevalence was comparable between cases (89.3%) and controls (91.2%; p = 0.8635), but cases had lower antibody levels (p = 0.022) at T0. Antibody levels increased at T6 and T12 but were not correlated with viremia clearance. BKPyV‐specific T cell responses to pools of overlapping 15mers (15mer peptide pool [15mP]) or immunodominant CD8 9mers (9mer peptide pool [9mP]) from the early viral gene region were not different between cases and controls at T0; however, clearance of viremia was associated with stronger 9mP responses at T6 (p = 0.042) and T12 (p = 0.048), whereas 15mP responses were not informative (T6 p = 0.359; T12 p = 0.856). BKPyV‐specific T cells could be expanded in vitro from all patients after transplant, permitting identification of 78 immunodominant 9mer epitopes including 50 new ones across different HLA class I. Thus, 9mP‐responses may be a novel marker of reconstituting CD8 T cell function that warrants further study as a complement of plasma BKPyV loads for guiding immunosuppression reduction. Abstract : Interferon‐γ ELISpot responses of CD8 T cells to immunodominant 9mer epitopes from the BK polyomavirus early viral gene region significantly increased in BK viremic patients but not in nonviremic controls, and are associated with viremia clearance posttransplantation, while standard 15mer T cell responses or antibody levels were uninformative.